INFORMATION SOCIETY AND NEW GLOBAL ETHICS - Tolstov , Ivan; Danilian, Vadym (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2023)
The article is dedicated to analyzing socio-cultural and ethical changes occurring in the modern information society under the influence of globalization processes. The main aim of the research is to analyze cultural transformations in the sphere of information society ethics. In examining these changes, the authors utilize theoretical concepts from leading researchers in the field of information society and ethics, including D. Bell, J. Baudrillard, M. Castells, R. Florida, at al. The article focuses on changes not only oriented towards technological aspects and the proliferation of information but also on the complex aspects of human interaction: the ability to create and transmit ethical values from generation to generation while considering existential priorities and moral norms. The authors regard the information society as a new socio-cultural reality that necessitates the development of a new global ethics. Such an ethics should take into account the global experience in the realm of morality and the necessity for democratizing the information society. The main emphasis of the article is directed towards interactive, networked communication as a key element of interaction, diverse forms of social dialogue, and methods of democratizing social relations through new technologies. In this context, the authors highlight the significance of Generation Z as a new creative class within the information society, serving as a subject of global ethics. This generation possesses new communicative skills and the ability to propose new strategies and forms of ethical behavior to adapt within the changing information society. In the conclusions of the article, the authors underscore that a new global ethics requires norms capable of aligning national, particular values with global universal ethical values, including ecological, humanistic, and human-centered values, ensuring their accessibility through the democratization of the information society. The methodological basis for such ethics could be Kantianism, fostering the harmonization of intergenerational interactions in the context of information society development.